2015
DOI: 10.1002/14651858.cd002786.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Medical adjuvant treatment to increase patency of arteriovenous fistulae and grafts

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 38 publications
2
56
1
Order By: Relevance
“…Aspirin : Conflicting results were found in RCT investigating the effect of aspirin therapy on access outcomes with two trials showing a marked reduction in thrombosis and one trial reporting an increase in thrombosis compared to placebo . Based on a meta‐analysis of these trials, the summary effect of aspirin on access thrombosis remained uncertain (odds ratio [OR] 0.40, 95% CI 0.07‐2.25, P = .3) . The most recent and largest RCT including 488 patients who received a new AVF, showed no significant reduction in access thrombosis, AVF abandonment or cannulation failure with low dose aspirin (100 mg daily) therapy compared to placebo (RR 1.09, 95% CI 0.72‐1.64)…”
Section: Clinical Trials Of Antiplatelet Agents and Vascular Access Omentioning
confidence: 99%
See 1 more Smart Citation
“…Aspirin : Conflicting results were found in RCT investigating the effect of aspirin therapy on access outcomes with two trials showing a marked reduction in thrombosis and one trial reporting an increase in thrombosis compared to placebo . Based on a meta‐analysis of these trials, the summary effect of aspirin on access thrombosis remained uncertain (odds ratio [OR] 0.40, 95% CI 0.07‐2.25, P = .3) . The most recent and largest RCT including 488 patients who received a new AVF, showed no significant reduction in access thrombosis, AVF abandonment or cannulation failure with low dose aspirin (100 mg daily) therapy compared to placebo (RR 1.09, 95% CI 0.72‐1.64)…”
Section: Clinical Trials Of Antiplatelet Agents and Vascular Access Omentioning
confidence: 99%
“…Ticlopidine : The effect of ticlopidine was studied in three RCT and meta‐analysis of these trial results suggested a reduction in access thrombosis (OR 0.45, 95% CI 0.25‐0.82, p = .009) …”
Section: Clinical Trials Of Antiplatelet Agents and Vascular Access Omentioning
confidence: 99%
“…Several studies have investigated the effectiveness of pharmacological therapy to improve patency of AV fistula during the peri-operative period, including antiplatelets, anticoagulants, statins, fish oil, and anti-hypertensive agents. Nonetheless, systemic reviews or meta-analysis showed controversial or no beneficial effects [34,35]. Currently, no pharmacotherapy has been recommended by the guidelines to promote AV fistula maturation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological interventions using aspirin, dipyridamole, fish oil, clopidogrel, and others have been generally unsuccessful or, when positive, have other studies showing conflicting results . A recent meta‐analysis of studies using fish oil did conclude, however, that omega‐3 polyunsaturated fatty acids supplementation probably protects against primary loss of arteriovenous access patency, with likely low to no effect on dialysis suitability failure, access interventions or access abandonment …”
Section: Arteriovenous Graft Complicationsmentioning
confidence: 99%